Przesłanki kształtowania struktury długu komunalnego w Polsce - Babczuk, Arkadiusz (The Rationale of Polish Municipal Debt Composition, 2009)
In this article, the author describes why municipalities choose a particular kind of debt instruments to run up municipal debt. After short theoretical literature review, results of empirical research are presented. Polish municipalities strongly prefer to minimize cost of municipal debt. Other criteria for selection debt instruments are underappreciated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 13-20